Papert, Parables, and the Future of Constructionism: A Constructionist Call for Action (Constructionism Conference Proceedings, 2025)
Constructionism approaches middle age at a time of political upheaval, battles over schooling, the emergence of accessible artificial intelligence tools, a rudderless edtech community, a maker movement in hibernation, official demands for computer science for all instruction, the teacher retention crisis, post-pandemic realignment, mobile computing ubiquity, and countless other forces generating chaos and noise. The constructionism community has much to offer in leading education and by extension, society, into an uncertain future, if it chooses to do so. This paper uses Seymour Papert as an object-to-think with to plot the future of constructionism and nurture the long-term health of the constructionist community.